Paternal characteristics associated with low birth weight in India - Sadashiva Hegde; Jang Bahadur Prasad; Rajeshwari Annappa Biradar; Alex Motes Carvalho (Indian Journal of Health Sciences and Biomedical Research KLEU, 2023)
BACKGROUND: There are both interim and long-standing effects of low birth weight, which is a significant global public health issue. Using data from the National Family Health Survey-5, which was conducted in 2019–21. AIM AND OBJECTIVE: This study aimed to determine the relationship between the father's attributes and low birth weight in India. Materials and Method: Both bivariate and multivariate approaches were used to analyze a total of 18,950 samples of families with kids. RESULT: The overall percentage of low birth weight in India was 16.6%. The highest prevalence of low birth weight was among younger fathers and mothers (17.6% and 18.2%), the father who went elementary school (16.7%), the mother non-educated (16.6%), paternal who had a drinking alcohol habit (15.3%), living in rural areas (15.3%), those belongs to Hindu religion (16.4%) and those from the central region (18%) of India. After accounting for major background influences, the adjusted odds ratios showed that, the paternal who have not completed more than a primary education, who is the Hindu religion, and who consume alcohol had the highest risk of LBW babies compared to their counterparts. CONCLUSION: This study demonstrated the incidence of low birth weight in India and how it relates to the characteristics of the father. The research will assist decision-makers in developing interventions to reduce low birth weight in India.